"Alternative facts" and St. Thomas Becket in the waning days of the Trump Presidency. Issue 3 (10th February 2022) - Cuenca, Esther Liberman
Abstract: This article examines the executive proclamation, issued by Donald Trump in late December 2020, celebrating the 850th anniversary of St. Thomas Becket's martyrdom. This executive proclamation is best seen as an example of the "alternative facts" that came to popularize the politics of the Trump era. Trump's Becket proclamation is an important text that represents the conservative push towards an understanding of history rooted in ideology but also in ahistorical and fictional representations of a medieval past. The Becket proclamation itself is medieval history filtered through the lens of conservative and grievance politics, which invoke the nebulous concept of personal or religious "liberty."